EXPERIMENTAL STUDY ON POWER PARAMETERS OF “ROLLING - ECA-PRESSING” COMBINED PROCESS - A. B. Naizabekov; S. N. Lezhnev; T. A. Koinov; E. A. Panin (Advanced Engineering Research, 2018)
Introduction.  Power  parameters  of  the  “rolling  −  equalchannel angular pressing” (ECA) combined process are studied. The work objective is to determine forces of rolling and pressing in the deformation by the combined method.Materials and Methods. The die strength calculation and the experiment on deformation of AISI 6063 aluminum samples were carried out. During the experiment, the force values were recorded using a strain-gauge station.Research Results. The strength analysis results show that this die design is suitable for creating an experimental stand of the “rolling − ECA-pressing” combined process, since the calculated  safety  margin  is  sufficient  to  implement  the  pressing under extreme conditions. The rolling forces at all stages of the  deformation  exceed  the  corresponding  pressing  forces, which is a necessary condition for the combined process. Discussion and Conclusions. The obtained results can be used in the design of experimental stands that implement the investigated combined  process. Herewith, the given  strain-gauge method for studying strength characteristics is suitable for the case of calibrated rolls.